2020
DOI: 10.1186/s12889-020-09049-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Epstein-Barr virus infection and infectious mononucleosis in the United Kingdom

Abstract: Background: Epstein-Barr Virus (EBV) is a ubiquitous gamma-herpesvirus with which~95% of the healthy population is infected. EBV infection has been implicated in a range of haematological malignancies and autoimmune diseases. Delayed primary EBV infection increases the risk of subsequent complications. Contemporaneous seroepidemiological data is needed to establish best approaches for successful vaccination strategies in the future. Methods: We conducted a sero-epidemiological survey using serum samples from 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 21 publications
(33 reference statements)
7
70
0
2
Order By: Relevance
“…Seroconversion from negative to positive for EBV Abs generally increases with age. It has a major incidence peak early in childhood and shows a second peak, especially for females, around puberty, co-incident with the approximate age of IM and co-incident with the female predominance in MS (3,103,104,106,(125)(126)(127)(128). EBV infection correlates with pediatric MS and essentially all children with MS are found to be positive for EBV Abs, whereas the positivity rate is considerably lower in healthy children (54,(129)(130)(131)(132).…”
Section: Ebv and Msmentioning
confidence: 99%
“…Seroconversion from negative to positive for EBV Abs generally increases with age. It has a major incidence peak early in childhood and shows a second peak, especially for females, around puberty, co-incident with the approximate age of IM and co-incident with the female predominance in MS (3,103,104,106,(125)(126)(127)(128). EBV infection correlates with pediatric MS and essentially all children with MS are found to be positive for EBV Abs, whereas the positivity rate is considerably lower in healthy children (54,(129)(130)(131)(132).…”
Section: Ebv and Msmentioning
confidence: 99%
“…[ 21 ] A recent study in the year 2020 done in United Kingdom also revealed overall increased EBV seroprevalence in the adolescent age group. [ 22 ] While a similar study by Winter et al; opined that EBV seroprevalence generally increases until around 24 years of age and remains constant thereafter. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection is present in 90% of human population [ 31 , 32 , 33 ]. The virus is transmitted through saliva, being usually asymptomatic during childhood; however, if the infection occurs in adolescence, it can lead to infectious mononucleosis (IM) [ 33 ]. In 1997, EBV was declared as the causal agent of nasopharyngeal carcinoma by the IARC [ 34 ].…”
Section: Epstein–barr Virus In Oral Cancermentioning
confidence: 99%